Exploring metastable states in UO2 using hybrid functionals and dynamical mean field theory. (15th December 2021) - Ratcliff, Laura E; Genovese, Luigi; Park, Hyowon; Littlewood, Peter B; Lopez-Bezanilla, Alejandro
Abstract: A detailed exploration of the f -atomic orbital occupancy space for UO2 is performed using a first principles approach based on density functional theory (DFT), employing a full hybrid functional within a systematic basis set. Specifically, the PBE0 functional is combined with an occupancy biasing scheme implemented in a wavelet-based algorithm which is adapted to large supercells. The results are compared with previous DFT + U calculations reported in the literature, while dynamical mean field theory is also performed to provide a further base for comparison. This work shows that the computational complexity of the energy landscape of a correlated f -electron oxide is much richer than has previously been demonstrated. The resulting calculations provide evidence of the existence of multiple previously unexplored metastable electronic states of UO2, including those with energies which are lower than previously reported ground states.